A two-week summer program promoting physical activity: quality of life assessment in Italian children. Issue 4 (21st April 2021) - Fainardi, Valentina; Fasola, Salvatore; Mastrorilli, Carla; Volta, Elio; La Grutta, Stefania; Vanelli, Maurizio
ABSTRACT: Physical activity (PA) can be associated with better health-related quality of life (HRQoL). This study aimed to assess HRQoL before and after a two-week summer program promoting PA in Italian school-aged children. Participants were recruited during the Giocampus summer 2017 (Parma, Italy), from June to July. Before (T0) and after (T1) the program, children and one of their parents answered the Kindl questionnaire. For each domain, least-square mean changes (LSmc) at T1 were derived from linear regression models stratified by responder and adjusted for child gender, age group, time spent in PAs and HRQoL score of the responder at T0. 350 children (7-13 years, 52% males) and 342 parents answered the questionnaire at both T0 and T1. At T1, the HRQoL score of the children significantly improved in the emotional (LSmc 2.9, p <0.001), self-esteem (LSmc 3.3, p <0.001), family (LSmc 4.2, p <0.001) and friend (LSmc 3.1, p <0.001) domains. Parents reported significantly more improvement in self-esteem than children (LSmc 6.7 vs 3.3, p =0.012). Children spending more time in PA reported significantly more improvement in self-esteem than those doing less PA (LSmc 4.4 [ p <0.001] vs 2.2 [ p =0.181]). A short summer program promoting PA may improve HRQoL in the general population of school-aged children.